(untitled) (Journal of actual problems of jurisprudence, 2018)
Water security represents particular importance for Kazakhstan as a state with a shortage of water resources and a large volume of rivers of transboundary knowledge. The theoretical aspects of this scientific concept are not fully covered in the literature and does not have a worthy justification and research. At the same time, relevance and necessity of research in this area is undeniable. The article analyzes of the concept and content of the Institute of water security given as a political and legal category.It considers such concepts as object, subject, threats, mechanism of ensuring with water security. In the analysis of domestic reality the current state of water security of Kazakhstan is considered. It is concluded that water security can not be considered only in the environmental and legal context, because it is a large, complex concept that combines economic and political components. The authors made some proposals on theoretical and practical significance by researching the current threats of external and internal character in the field of water security. Key words: water law, water security, national security, national interests, threats to water security, threats to national security.